PERBANDINGAN PENYELESAIAN SENGKETA PERUSAHAAN MELALUI LITIGASI DAN NON LITIGASI: PERSPEKTIF PERLINDUNGAN HUKUM HAK ASASI MANUSIA - Mona Wulandari; Desni Raspita; Hendra Apriyanto (The Juris, 2026)
Rapid societal advancement inevitably gives rise to disputes. Dispute resolution efforts can be pursued through two avenues: litigation and non-litigation. Non-litigation options include deliberation, mediation, and arbitration. Court-based resolution (litigation) is often time-consuming and costly, frequently resulting in one satisfied party and one dissatisfied party. Conversely, non-litigation methods such as mediation, negotiation, or arbitration are considered more efficient and better at preserving relationships between the disputing parties. This study employs a normative-juridical research method. The findings indicate that, despite the shortcomings inherent in the judicial process, the judiciary must be maintained as a "pressure valve" within a state governed by the rule of law and democracy. However, its position needs to shift to that of a "last resort," while alternative mechanisms are positioned as the "first resort." This line of thinking requires further development. Courts cannot simply be abolished in a democratic state governed by the rule of law, as they serve as the foundation upon which alternative dispute resolution mechanisms were established. The study demonstrates that dispute resolution whether through litigation or non-litigation combined with planned risk management, is key to maintaining operational continuity and business sustainability; success depends on agreements that offer "win-win solutions," thereby upholding human rights protections.